ANALISIS FAKTOR PENGHAMBAT PELAKSANAAN EKSTRAKURIKULER BOLA BASKET DI SMP ISLAM INSAN CENDIKIA MEMPAWAH - Nurhani Nurhani; Fitriana Puspa Hidasari; Mimi Haetami (Universitas Tanjungpura, 2020)
AbstractThis study aims to analyze the inhibiting factors in the implementation of basketball extracurricular activities at the Insan Cendikia Mempawah Islamic Middle School. This research is a survey research. This study was conducted by using a questionnaire in data collection. As for the stages in the process of data collection including the implementation of research and examination of data The subjects in this study were students who took part in basketball extracurricular activities at the Islamic Middle School Insan Cendikia Mempawah. In the research results, basketball extracurricular activities internal factors which include psychological aspects which have a percentage of 67% and then psychological aspects have a percentage of 33%. In the analysis of the inhibiting factors of basketball extracurricular implementation there are also external factors, where the social environment aspect has a percentage of 22.23%, facilities and infrastructure with a percentage of 16.67%, non-social environment with a percentage of 33.48% and a learning approach with a percentage of 27.62%. Keywords: Inhibiting factors, Extracurricular, Basketbal